Marine Tourism Development in Mattiro Matae Village Liukang Tupabbiring District Pangkajene and Islands Regency: Defining Minawisata Concept - St. Nur Annisa; Nurul Istiqamah Ulil Albab; Khairul Sani Usman (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Minawisata is an economic development that integrates the marine, fisheries, and tourism sectors. Mattiro Matae Village, as a marine conservation area, has great potential to become a center for conservation-based marine tourism. This study aims to assess land suitability and formulate a strategy for developing minawisata in the village. Using quantitative descriptive methods, data were collected through observation, interviews, and documentation. Data analysis was carried out using land suitability analysis and SWOT. The results of the study showed that Mattiro Matae Village has a tourism suitability index of 100% for the fisheries sector, indicating enormous potential. However, the development of minawisata in this village still faces challenges, such as suboptimal local government management and low public understanding of the importance of conservation. Based on the SWOT analysis, the strategies for developing minawisata in Mattiro Matae Village include leveraging natural beauty and biodiversity, improving accessibility and public facilities, implementing environmental monitoring systems, and providing training and education to enhance community involvement and awareness of conservation